Cognitive interventions for memory and psychological well-being in aging and dementias - Dinius, Cassandra J.; Pocknell, Carmen E.; Caffrey, Michelle P.; Roche, Richard A. P. (Frontiers in Psychology, 2023)
The human lifespan has expanded drastically in the last few centuries, due to improvements in sanitation, medicine and nutrition, but with this increase in longevity comes higher rates of cognitive pathology such as mild cognitive impairment (MCI) and dementia; the latter is estimated to reach more than 75 million people by 2030. Pathology risk is related to measures of executive function, lifestyle factors (e.g., education, occupation, leisure activities) and cognitive reserve. One way of building cognitive reserve may be to structure the environment to encourage lifelong engagement and learning, and since a pharmacological “cure” for dementia remains elusive, non-pharmacological approaches such as physical activity, social engagement and cognitive stimulation are becoming increasingly essential to preserving and protecting brain health. Here we describe our recent research into Reminiscence Therapy (RT) to promote cognitive and psychological function in old age and early dementia. We review the Recall Initiative, which involved brain imaging and behavioural indices of memory pre- and post-RT. We also report results from a pilot study – AIM WARM – in which RT was combined with physical activity, specifically walking, for early-stage dementia. Finally, we outline our future directions for tailored reminiscence interventions in combination with other activities (e.g., yoga, meditation) for different groups, namely early Alzheimer’s Disease, Semantic Dementia and older individuals in the prison system.